2014
DOI: 10.1093/brain/awu100
|View full text |Cite
|
Sign up to set email alerts
|

Differential influence of hippocampal subfields to memory formation: insights from patients with temporal lobe epilepsy

Abstract: To clarify the anatomical organization of human memory remains a major challenge in clinical neuroscience. Experimental data suggest dentate gyrus granule cells play a major role in memory acquisition, i.e. pattern separation and rapid pattern completion, whereas hippocampal CA1 neurons are implicated in place memory and autobiographical memory retrieval. Patients with temporal lobe epilepsy present with a broad spectrum of memory impairment, which can be assessed during clinical examination. Although long sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
132
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(145 citation statements)
references
References 57 publications
7
132
1
5
Order By: Relevance
“…Studies with TLE patients have shown that neuron loss in specific hippocampal subfields can promote differential memory loss (Coras et al, 2014;Rodrigues et al, 2015). Besides, SRS might cause progressive cognitive decline (Sutula et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with TLE patients have shown that neuron loss in specific hippocampal subfields can promote differential memory loss (Coras et al, 2014;Rodrigues et al, 2015). Besides, SRS might cause progressive cognitive decline (Sutula et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…26 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) 36 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) 85 (91) 62 (67) Type 1 70 (74) 33 (47) 38 (54) 27 (39) 13 (19) 6 (3-10) (25) 7 (30) 11 (48) 5 (22) 7 ( 42 (43) 58 (60) 22 (23) 19 (20) 8 (4-13)…”
Section: (4-15)unclassified
“…26 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) 38 (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) 61 (85) 49 (68) Type 2 24 (25) 8 (33) 16 (67) 7 (29) 6 (25) 7 ( 44-45% of the selected population, but only 11% were affected by DP. The distribution of HS types (74% type 1, 25% type 2, and only one patient with type 3) is slightly different from that reported in some studies, 12,14,15,22 but similar to the recent findings of Savitr Sastri et al, 25 and confirms that type 1 is the most frequent, whereas CA4-predominant type 3 is rare, accounting for no more than approximately 4% of the patients in some cohorts, 4,14,15 and none at all in others.…”
Section: (4-12)mentioning
confidence: 99%
“…Further, the cytoarchitectural subdivisions (or ‘subfields') of the hippocampus are associated with distinct functions. For example, the dentate gyrus (DG) and sectors 3 and 4 of the cornu ammonis (CA) are involved in declarative memory acquisition12, the subiculum and CA1 play a role in disambiguation during working memory processes13, and the CA2 is implicated in animal models of episodic time encoding14 and social memory15. The anterior hippocampus, which includes the fimbria, CA subregions and hippocampal -amygdaloid transition area (HATA), may be involved in the mediation of cognitive processes including imagination, recall and visual perception16 and anxiety-related behaviours17.…”
mentioning
confidence: 99%